THE DESTRUCTION OF CULTURAL HERITAGE IN INTERNATIONAL HUMANITARIAN LAW PERSPECTIVE: CASE STUDY OF ISIS - Aris Fadillah (FH 16UMY 036, 2016)
The protection of cultural heritage is being questioned by the ISIS campaign of destruction of cultural heritage recently. The massive and systematic destruction spread out around Iraq and Syria. As prima facie, at least seven of UNESCO World List Heritage has faced deliberate and intentional destruction. ISIS argued that the destruction is the form of religious purification, however, media propaganda seems like more dominant. Lately, international community spoke up and stand up together to condemn the ISIS action as a war crime. International humanitarian law has been determined to prohibit the destruction of cultural heritage. In fact, there is ambiguous and unclear provision related to the sanction, and even more the implementation of its. Meanwhile, this research purposed to understand the reason behind ISIS action and the international humanitarian law regulated the destruction. Furthermore, the type of this research is normative legal research with statute approach and case approach. In addition, by using a juridical qualitative and descriptive method, the research result shows some reasons behind ISIS destruction namely theology, cultural cleansing, economy, iconoclasm and propaganda. Then, the international humanitarian law determines the ISIS destruction as a serious violation and shall be punished and held responsible for the criminal sanctions. It formulated the suggestion for international community to be more pro-active in preventing the destruction either in peacetime or armed conflict, and also created a clear provision related to enforcement mechanism and jurisdiction. Keywords: Cultural Heritage, ISIS, and International Humanitarian Law